GAMBARAN PENGETAHUAN IBU HAMIL TRIMESTER III TENTANG TANDA-TANDA PERSALINAN DI BPM SUTINAH,SST TARUMAJAYA KABUPATEN BEKASI PERIODE MARET – APRIL TAHUN 2019 - Siti Umamah; Ufi Aprillia (LPPM STIKes Prima Indonesia, 2020)
In Indonesia, the maternal mortality rate is still high, based on the 2015 inter-census population survey, thematernal mortality rate in Indonesia is 305 per 100,000 live births. This figure is still high from the target of 126per 100,000 (IDHS, 2015). This study aims to determine the frequency distribution of pregnant women's knowledgeabout the signs of birth in BPM Sutinah Midwife, S.ST. The analysis technique s Univariate analysis, all dataanalysis obtained from the help of SPSS software. The instrument in this study was a questionnaire. Data iscollected using primary data. The respondent variables in this study were knowledge of third-trimester pregnantwomen about signs of labor, and the independent variables in this study were age, education, employment, parity,and sources of information.The results of the study illustrate the knowledge of mothers who have good knowledgethere are seven mothers (19.4%), consisting of 4 mothers (11.1%) who are aged 20-35 years, five mothers (13.9%)mothers who do not work, six mothers (16.7%) were multiparous, and five mothers (13,%) received informationabout signs of labor from health workers. It is expected that health workers can provide health education aboutchildbirth, signs of labor and provide motivation for pregnant women and families so that the knowledge ofpregnant women about signs of labor gets better than before.